Charismatic Christianity in Finland, Norway, and Sweden : Case Studies in Historical and Contemporary Developments - Moberg, Jessica; Skjoldli, Jane; Moberg, Jessica; Skjoldli, Jane (Basingstoke Springer Nature, 2018)
Pentecostal; Renewal; Televangelism; Scandanavia; Nordic
English
Keywords: Religion & beliefs; Pentecostal; Renewal; Televangelism; Scandanavia; Nordic